Preparation method of carbon layer coated copper-based sulfide

The use of glucose to form carbon shell-coated copper-based sulfides by solvothermal method, solving the problems of insufficient stability of transition metal sulfides and complex large-scale production, and achieving high stability and efficient catalysis of the catalyst.

CN119706789AActive Publication Date: 2025-03-28NINGBO DIGITAL TWIN (EASTERN UNIV OF TECH) RES INST +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411868530.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-28
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

Transition metal sulfides are insufficient in long-term operation or extreme environments, the active sites are prone to inactivate, and large-scale production is complex, making it difficult to maintain high performance and low cost.

Method used

The solvent-thermal method is used to use glucose as the carbon source to form a uniform carbon shell coated copper-based sulfide core, which improves the stability and durability of the catalyst.

Benefits of technology

Provides physical barriers and regulates electron transport paths through carbon-covered structures, improves catalytic stability and efficiency, and makes catalysts easy to produce and commercially promote on a large scale.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706789A_ABST
    Figure CN119706789A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a carbon layer coated copper-based sulfide, and the preparation method specifically comprises the following steps: S1, mixing CuCl2. 2H2O, Na2S. 9H2O and NaCl, fully grinding, and sequentially carrying out calcination treatment, washing treatment and drying treatment to obtain a core; and S2, glucose is dissolved in deionized water, then hydrochloric acid is added to obtain a mixture, the mixture is stirred, the core obtained in the step S1 is added, ultrasonic treatment and hydrothermal treatment are sequentially performed, then the mixture is cooled to the room temperature, centrifugation, washing and drying treatment are sequentially performed, and finally calcination treatment is performed to obtain the carbon layer coated copper-based sulfide. Compared with the prior art, glucose is used as a carbon source through a solvothermal method, a layer of uniform carbon shell is formed to wrap a copper-based sulfide core, and the layer of carbon not only can provide a physical barrier to prevent an internal material from being directly exposed to a severe environment, but also can adjust an electron transmission path; meanwhile, the carbon-coated structure can optimize charge transfer kinetics, a new active site is possibly introduced, the catalytic efficiency is further improved, the glucose which is a cheap and universally available raw material is adopted, a relatively simple solvothermal synthesis method is combined, and the preparation method is simple and easy to implement. And the catalyst is easy to produce on a large scale and commercially popularize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrocatalysis, and in particular relates to a method for preparing copper-based sulfide coated with a carbon layer. Background Art

[0002] Electrocatalysis is a technology that accelerates the rate of chemical reactions by applying an external electric potential. It plays a key role in energy conversion and storage, such as water electrolysis to produce hydrogen, fuel cells, and carbon dioxide reduction. As a clean, efficient and sustainable method, electrocatalysis not only helps reduce dependence on fossil fuels, but also significantly reduces carbon emissions, which is of great significance for promoting a green energy economy.

[0003] In recent years, transition metal sulfides have gained wide attention in the field of electrocatalysis due to their unique electronic structures and physicochemical properties. They have shown excellent catalytic activity, especially in oxygen evolution reaction (OER), hydrogen evolution reaction (HER) and nitrogen reduction reaction (NRR). In addition, TMS materials have the advantages of high cost-effectiveness, high abundance and environmental friendliness, making them a potential alternative to precious metal-based catalysts.

[0004] Although TMS materials perform well under laboratory conditions, they face many challenges in practical applications. The main problems include: Insufficient stability: In long-term operation or extreme working environments, such as high temperature, high pressure or strong acid and alkali environments, TMS is prone to corrosion or oxidation, causing its catalytic performance to decline rapidly. Active sites are easily deactivated: The active sites on the surface of the catalyst may lose activity due to coverage by adsorbates, affecting the catalytic efficiency. Complexity of large-scale production: Maintaining consistent high performance and low-cost production remains a challenge during the scale-up process from laboratory to industrial scale. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a carbon layer-coated copper-based sulfide, which uses cheap glucose as a carbon source and is coated by a solvent thermal method, and has broad application prospects in effectively improving the stability of transition metal-based catalysts.

[0006] The present invention provides a method for preparing a carbon layer-coated copper-based sulfide, the preparation method specifically comprising the following steps:

[0007] S1, CuCl2.2H2O, Na2S.9H2O and NaCl are mixed and fully ground, and then calcined, washed and dried in sequence to obtain a core;

[0008] S2, dissolving glucose in deionized water, then adding hydrochloric acid and stirring, adding the core obtained in step S1, sequentially subjecting to ultrasonic treatment and hydrothermal treatment, then cooling to room temperature and sequentially subjecting to centrifugation, washing and drying, and finally subjecting to calcination to obtain a carbon layer-coated copper-based sulfide.

[0009] Compared with the prior art, the present invention uses glucose as a carbon source through a solvothermal method to form a uniform carbon shell that wraps around the copper-based sulfide core. This layer of carbon can not only provide a physical barrier to prevent the internal material from being directly exposed to a harsh environment, but also regulate the electron transfer path, thereby improving the overall catalytic stability and durability. At the same time, the carbon coating structure can optimize the charge transfer dynamics and may introduce new active sites to further improve the catalytic efficiency. In addition, the present invention uses glucose, a cheap and widely available raw material, combined with a relatively simple solvothermal synthesis method, so that the catalyst is easy to mass produce and commercialize.

[0010] In a possible implementation, in step S1, the mass ratio of CuCl2.2H2O to Na2S.9H2O is 1:1, and the mass ratio of CuCl2.2H2O to NaCl is 1:10.

[0011] Compared with the prior art, the mass ratio of CuCl2.2H2O and Na2S.9H2O in the present invention is 1:1, and this ratio ensures that the two reactants are close to the ideal stoichiometric ratio, so that copper ions (Cu2+) and sulfur ions (S2-) can react as completely as possible to generate the target product, copper-based sulfide. Such a ratio helps to obtain high-purity, uniformly distributed sulfide particles, which is crucial for catalytic activity. At the same time, the appropriate ratio of CuCl2·2H2O to Na2S·9H2O can effectively control the growth rate and morphology of the crystal. Excessive amounts of either party may lead to the formation of by-products or uncontrolled crystal growth, thereby affecting the physical properties and catalytic performance of the final material. Maintaining a ratio of 1:1 helps to obtain a nanostructure with suitable size and good dispersion, which is particularly beneficial to improving catalytic efficiency.

[0012] Adding an appropriate amount of NaCl can play several roles: 1. Inhibiting agglomeration: The presence of NaCl can prevent the agglomeration of copper-based sulfide particles to a certain extent and promote more uniform dispersion; 2. Regulating the reaction environment: NaCl can change the ionic strength of the solution, thereby affecting the reaction kinetics, making the reaction milder and easier to control; 3. Template effect: In some cases, NaCl crystals can act as temporary templates during the synthesis process to help form sulfide particles of a specific shape.

[0013] In a possible implementation, in step S1, the parameters of the calcination treatment are as follows: temperature is 60° C., and time is 30 min.

[0014] Compared with the prior art, the advantages of the present invention using the above calcination parameters are: treatment at a relatively low temperature (such as 60° C.) can avoid structural damage or component volatilization caused by high temperature, which is very important for maintaining the original structure and composition of copper-based sulfides. Especially when the goal is to prepare nano-scale materials, too high a temperature may cause particle agglomeration or excessive crystal growth, thereby affecting the catalytic performance of the final product.

[0015] In a possible implementation, in step S1, the washing treatment uses deionized water and ethanol respectively, and the drying treatment temperature is 40°C.

[0016] Compared with the prior art, the present invention first uses deionized water for washing, which can effectively remove inorganic salts and other water-soluble impurities generated during the reaction and ensure the purity of the sample. The subsequent use of ethanol for washing helps to further remove residual moisture and organic impurities on the surface, while reducing the moisture content in the subsequent drying process. 40°C is a relatively low temperature, which can effectively remove residual moisture and ethanol without destroying the material structure. This is very important for maintaining the original form and composition of copper-based sulfides, especially when the material is nanoscale, as excessively high temperatures may cause particle agglomeration or excessive crystal growth.

[0017] In a possible implementation, in step S2, the concentration of glucose in the mixture is 0.006-0.03 g / ml, and the concentration of hydrochloric acid is 0.0005-0.003%.

[0018] Compared with the prior art, the present invention sets the concentration of glucose between 0.006-0.03g / ml, which helps to ensure sufficient carbon source supply, but not too much to cause balling. Such a concentration can promote the carbon layer to be evenly coated on the surface of the copper-based sulfide, rather than forming independent carbon balls. Appropriate carbon coating can not only protect the internal active substances from corrosion, but also provide additional conductive paths and enhance catalytic performance. Glucose as a carbon source provides sufficient raw materials to build a carbon shell of moderate thickness. As the amount of carbon source added increases, the thickness of the carbon layer gradually increases, but at the above concentration, the carbon layer will not be too thick to affect the exposure of the active sites of the internal copper-based sulfide. A carbon layer of appropriate thickness can maintain good catalytic activity while protecting the internal structure.

[0019] At the same time, the hydrochloric acid concentration of the present invention is set at 0.0005-0.003%. As the acid concentration increases, the ability of glucose to automatically form balls will also increase. Therefore, maintaining a low acid concentration can effectively inhibit the self-assembly of glucose into balls, thereby avoiding the formation of unnecessary by-products. This ensures that the main product is a coated rather than dispersed carbon ball, thereby improving the consistency and controllability of the material.

[0020] In a possible implementation, in step S2, the ultrasonic treatment time is 30 minutes.

[0021] Compared with the prior art, the ultrasonic treatment of the present invention can produce strong mechanical vibration and cavitation effect, effectively break up the agglomerated particles, and make the copper-based sulfide and glucose and other components more evenly dispersed in the solution, which is crucial for forming a uniform carbon coating, because any unevenness may lead to a decrease in catalytic performance. Ultrasonic waves can significantly increase the frequency of collisions between molecules, thereby promoting contact and reaction rate between reactants. In particular, in the solvothermal synthesis process, ultrasonic treatment helps to accelerate the decomposition and carbonization process of glucose, so that the carbon layer can be evenly deposited on the surface of the copper-based sulfide in a relatively short time.

[0022] In a possible implementation, in step S2, the parameters of the hydrothermal treatment are as follows: temperature is 170-210° C., and time is 2-10 h.

[0023] The inventors have experimentally verified that effective carbon coating cannot be performed at 150°C. Therefore, the temperature of the hydrothermal treatment is set within the range of 170-210°C to ensure sufficient heat to start and accelerate the carbonization process. This temperature range can not only activate the decomposition and carbonization reaction of glucose, but also promote the uniform deposition of the carbon layer on the surface of the copper-based sulfide. As the temperature rises, the carbon layer coating speed becomes faster and faster, which means that at a higher temperature of 170-210°C, efficient carbon coating can be achieved in a shorter time, thereby shortening the production cycle and increasing output. At the same time, higher temperatures help to form a denser and more stable carbon layer structure, enhancing the stability and catalytic performance of the material.

[0024] In addition, under fixed temperature, by adjusting the hydrothermal time (2-10 hours), hydrothermal treatment can generate a coating material with a hexagonal nanosheet structure. This unique morphology can not only provide a larger specific surface area and increase the number of active sites, but also improve the electron transfer path and further enhance the catalytic efficiency. Therefore, setting the hydrothermal time can precisely control the thickness of the carbon coating layer. A shorter time is suitable for preparing thin-layer coating materials, while a longer time allows the formation of a thicker carbon layer.

[0025] In a possible implementation, in step S2, deionized water and ethanol are used for washing respectively.

[0026] Compared with existing technologies, the use of deionized water can first effectively remove inorganic salts and other water-soluble impurities produced during the reaction, ensuring the purity of the sample, and then further washing with ethanol helps to remove residual moisture and other organic impurities on the surface, such as incompletely reacted glucose or by-products. As a non-polar solvent, ethanol can help disperse the nanoparticles and prevent them from agglomerating due to interactions, thereby ensuring the uniformity and stability of the final product. Good dispersibility is essential to maintaining the high activity and long life of the catalyst.

[0027] In a possible implementation, in step S2, the parameters of the drying process are as follows: temperature is 40° C., and time is 12 hours.

[0028] Compared with existing technologies, 40°C is a relatively low temperature that can effectively remove residual moisture and ethanol without destroying the material structure, which is very important for maintaining the original morphology and composition of copper-based sulfides and their carbon coatings, especially when the material is nanoscale, where too high a temperature may cause particle agglomeration or excessive crystal growth; and the longer drying time of 12 hours ensures that the sample can be fully dried, effectively removing all moisture inside and on the surface even for more complex structures or larger sample volumes. This helps avoid subsequent problems caused by residual moisture, such as unstable material properties or chemical changes during storage.

[0029] In a possible implementation, in step S2, the parameters of the calcination treatment are as follows: temperature is 700° C., time is 2 h, and atmosphere is argon.

[0030] Compared with the prior art, the present invention adopts the above calcination treatment parameters, wherein 700°C is a relatively high temperature, which can provide sufficient energy to drive the phase change process inside the material, so that the copper-based sulfide is more completely converted into the target phase. At the same time, the high temperature helps to improve the crystallinity of the material and form a more regular and stable crystal structure, which has a significant effect on the catalytic performance. The calcination time of 2 hours is long enough to ensure that all necessary physical and chemical changes are completed, but not too long to cause excessive sintering or structural damage of the material. Such a time setting can improve production efficiency and reduce energy consumption while ensuring quality. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 They are the SEM image and TEM image of the copper-based sulfide prepared in Example 1;

[0032] Figure 2 They are respectively the SEM image and TEM image of the copper-based sulfide prepared in Example 2;

[0033] Figure 3They are respectively the SEM image and TEM image of the copper-based sulfide prepared in Example 3;

[0034] Figure 4 They are respectively the SEM image and TEM image of the copper-based sulfide prepared in Example 4;

[0035] Figure 5 They are the SEM image and TEM image of the copper-based sulfide prepared in Example 5;

[0036] Figure 6 They are the SEM image and TEM image of the copper-based sulfide obtained in Example 6;

[0037] Figure 7 They are respectively the SEM image and TEM image of the copper-based sulfide obtained in Example 7;

[0038] Figure 8 They are respectively the SEM image and TEM image of the copper-based sulfide prepared in Example 8;

[0039] Fig. 9 They are respectively the SEM image and TEM image of the copper-based sulfide prepared in Example 9;

[0040] Fig.10 They are respectively the SEM image and TEM image of the copper-based sulfide obtained in Example 10;

[0041] Fig.11 They are respectively the SEM image and TEM image of the copper-based sulfide obtained in Example 11;

[0042] Fig.12 They are respectively the SEM image and TEM image of the copper-based sulfide obtained in Example 12;

[0043] Fig.13 They are respectively the SEM image and TEM image of the copper-based sulfide obtained in Example 13;

[0044] Fig.14 They are respectively the SEM image and TEM image of the copper-based sulfide obtained in Example 14;

[0045] Fig.15 The oxygen evolution reaction performance test results of the copper-based sulfide prepared in Example 3 are shown. DETAILED DESCRIPTION

[0046] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.

[0047] It should be noted that the endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.

[0048] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, terms with conventionally understood meanings are defined herein for the purpose of clarification or ease of reference, and such definitions herein should not be construed as indicating significant differences from conventional understandings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods. Unless otherwise stated, the use of commercially available kits, reagents and instruments is carried out in accordance with the protocols and parameters given by the manufacturer.

[0049] The technical effects of the present invention are described below in conjunction with specific embodiments.

[0050] Example 1

[0051] This embodiment provides a carbon layer-coated copper-based sulfide, which is prepared by the following preparation method:

[0052] S1, 200mg CuC l2 .2H2O, 200mg Na2S.9H2O and 2g NaCl were mixed and ground thoroughly, and calcined in a muffle furnace at 60°C for 30min, then washed with deionized water and ethanol, and dried in a vacuum oven at 40°C to obtain a core;

[0053] S2, 0.5g glucose was dissolved in 30mL deionized water, then 15μL hydrochloric acid was added and stirred for 20min, then 35mg of calcined copper-based sulfide was added and ultrasonicated for 30min to make the solid dispersed evenly in the solution. And hydrothermal at 150℃ for 10h, after cooling to room temperature, centrifugal washing with water and ethanol was performed, and dried in a vacuum drying oven at 40℃ for 12h, and calcined at 700℃ for 2h in an Ar atmosphere to obtain copper-based sulfide.

[0054] Example 2

[0055] This embodiment provides a carbon layer-coated copper-based sulfide, which is different from Embodiment 1 only in that the temperature of the hydrothermal treatment in this embodiment is 170° C. The rest is the same as Embodiment 1 and will not be described again.

[0056] Example 3

[0057] This embodiment provides a carbon layer-coated copper-based sulfide, which is different from Embodiment 1 only in that the temperature of the hydrothermal treatment in this embodiment is 190° C. The rest is the same as Embodiment 1 and will not be described again.

[0058] Example 4

[0059] This embodiment provides a carbon layer-coated copper-based sulfide, which is different from Embodiment 1 only in that the temperature of the hydrothermal treatment in this embodiment is 210° C. The rest is the same as Embodiment 1 and will not be described again.

[0060] Example 5

[0061] This embodiment provides a carbon layer-coated copper-based sulfide, which is different from Embodiment 3 only in that the hydrothermal treatment time in this embodiment is 2 hours, and the rest is the same as Embodiment 3, which will not be repeated here.

[0062] Example 6

[0063] This embodiment provides a carbon layer-coated copper-based sulfide, which is different from Embodiment 3 only in that the hydrothermal treatment time in this embodiment is 6 hours, and the rest is the same as Embodiment 3, which will not be repeated here.

[0064] Example 7

[0065] This embodiment provides a carbon layer-coated copper-based sulfide, which is different from Embodiment 3 only in that the hydrothermal treatment time in this embodiment is 14 hours, and the rest is the same as Embodiment 3, which will not be repeated here.

[0066] Example 8

[0067] This embodiment provides a carbon layer-coated copper-based sulfide, which is different from Embodiment 3 only in that the hydrothermal treatment time in this embodiment is 18 hours, and the rest is the same as Embodiment 3, which will not be repeated here.

[0068] Example 9

[0069] This embodiment provides a carbon layer-coated copper-based sulfide, which is different from Embodiment 3 only in that hydrochloric acid is not added in this embodiment, and the rest is the same as Embodiment 3, which will not be described again here.

[0070] Example 10

[0071] This embodiment provides a carbon layer-coated copper-based sulfide, which is different from Embodiment 3 only in that the amount of hydrochloric acid added in this embodiment is 50 μL, and the rest is the same as Embodiment 3, which will not be repeated here.

[0072] Embodiment 11

[0073] This embodiment provides a carbon layer-coated copper-based sulfide, which is different from Embodiment 3 only in that the amount of hydrochloric acid added in this embodiment is 100 μL, and the rest is the same as Embodiment 3, which will not be repeated here.

[0074] Example 12

[0075] This embodiment provides a carbon layer-coated copper-based sulfide, which is different from Embodiment 3 only in that glucose is not added in this embodiment, and the rest is the same as Embodiment 3, which will not be described again here.

[0076] Embodiment 13

[0077] This embodiment provides a carbon layer-coated copper-based sulfide, which is different from Embodiment 3 only in that the amount of glucose added in this embodiment is 0.25 g, and the rest is the same as Embodiment 3, which will not be repeated here.

[0078] Embodiment 14

[0079] This embodiment provides a carbon layer-coated copper-based sulfide, which is different from Embodiment 3 only in that the amount of glucose added in this embodiment is 1 g, and the rest is the same as Embodiment 3, which will not be repeated here.

[0080] The inventors tested the properties of the copper-based sulfides obtained in Examples 1 to 14, respectively. Figure 1 The SEM and TEM images of the copper-based sulfide prepared in Example 1 are respectively, Figure 2 The SEM and TEM images of the copper-based sulfide obtained in Example 2 are respectively, Figure 3 The SEM and TEM images of the copper-based sulfide obtained in Example 3 are respectively, Figure 4 The SEM and TEM images of the copper-based sulfide obtained in Example 4 are respectively, Figure 5 The SEM and TEM images of the copper-based sulfide obtained in Example 5 are respectively, Figure 6 The SEM and TEM images of the copper-based sulfide obtained in Example 6 are respectively, Figure 7 The SEM and TEM images of the copper-based sulfide obtained in Example 7 are respectively, Figure 8 They are the SEM and TEM images of the copper-based sulfide obtained in Example 8, Fig. 9 The SEM and TEM images of the copper-based sulfide obtained in Example 9 are respectively, Fig.10 They are the SEM and TEM images of the copper-based sulfide obtained in Example 10, Fig.11 The SEM and TEM images of the copper-based sulfide obtained in Example 11 are respectively, Fig.12 The SEM and TEM images of the copper-based sulfide obtained in Example 12 are respectively, Fig.13 The SEM and TEM images of the copper-based sulfide obtained in Example 13 are respectively, Fig.14 They are the SEM and TEM images of the copper-based sulfide prepared in Example 14, respectively.

[0081] 3 mg of the copper-based sulfide prepared in Example 3 was added with 300 μL of deionized water, 300 μL of ethanol and 30 μL of 5% Nafion, and ultrasonicated for 30 min to form a suspension. 100 μL of the suspension was applied to a 1*1 cm 2 The oxygen evolution reaction performance was tested on carbon paper after drying. The oxygen evolution reaction stability was tested at a constant potential of 1.6V. The results are shown in Fig.15 shown.

[0082] from Figure 1-Figure 15 The results show that: 1. Hydrothermal temperature: can control the rate of carbon layer coating. Coating is not possible at 150°C. As the temperature increases, the carbon layer coating speed becomes faster and faster.

[0083] 2. Hydrothermal time: When the temperature is fixed, the hexagonal nanosheet coating material is hydrothermally generated. As the hydrothermal time increases, the thickness of the carbon coating layer gradually increases.

[0084] 3. Amount of acid added: When no acid is added, a non-fixed-shape coating material is formed. As the acid concentration increases, the ability of glucose to automatically form balls increases, forming carbon balls instead of coating materials;

[0085] 4. Effect of different carbon source addition amounts: In the absence of glucose, amorphous small particles are formed. As the amount of carbon source added increases, the thickness of the carbon layer also increases.

[0086] 5. Application potential: The presence of the carbon layer can effectively improve the stability of the material and avoid the deactivation of the catalyst.

[0087] It can be seen from the above results that the present invention uses glucose as a carbon source through a solvothermal method to form a uniform carbon shell that wraps the copper-based sulfide core. This layer of carbon can not only provide a physical barrier to prevent the internal material from being directly exposed to a harsh environment, but also regulate the electron transfer path, thereby improving the overall catalytic stability and durability. At the same time, the carbon coating structure can optimize the charge transfer dynamics and may introduce new active sites to further improve the catalytic efficiency. In addition, the present invention uses glucose, a cheap and widely available raw material, combined with a relatively simple solvothermal synthesis method, so that the catalyst is easy to mass produce and commercialize.

[0088] Although the disclosure is disclosed as above, the protection scope of the disclosure is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the disclosure, and these changes and modifications will fall within the protection scope of the present invention.

Claims

1. A method for preparing a carbon layer-coated copper-based sulfide, characterized in that: The preparation method specifically comprises the following steps: S1, CuCl2.2H2O, Na2S.9H2O and NaCl are mixed and fully ground, and then calcined, washed and dried in sequence to obtain a core; S2, dissolving glucose in deionized water, then adding hydrochloric acid to obtain a mixture and stirring it, adding the core obtained in step S1, sequentially subjecting it to ultrasonic treatment and hydrothermal treatment, then cooling it to room temperature and sequentially subjecting it to centrifugation, washing and drying, and finally calcining it to obtain a carbon layer-coated copper-based sulfide.

2. The preparation method according to claim 1, characterized in that In the step S1, the mass ratio of CuCl2.2H2O to Na2S.9H2O is 1:1, and the mass ratio of CuCl2.2H2O to NaCl is 1:

10.

3. The preparation method according to claim 1, characterized in that: In step S1, the parameters of the calcination treatment are as follows: temperature is 60° C., and time is 30 min.

4. The preparation method according to claim 1, characterized in that: In the step S1, the washing process uses deionized water and ethanol respectively, and the temperature of the drying process is 40°C.

5. The preparation method according to claim 1, characterized in that: In step S2, the concentration of glucose in the mixture is 0.006-0.03 g / ml, and the concentration of hydrochloric acid is 0.0005-0.003%.

6. The preparation method according to claim 1, characterized in that: In step S2, the ultrasonic treatment time is 30 minutes.

7. The preparation method according to claim 1, characterized in that: In step S2, the parameters of the hydrothermal treatment are as follows: temperature is 170-210° C., and time is 2-10 h.

8. The preparation method according to claim 1, characterized in that: In step S2, deionized water and ethanol are used for washing respectively.

9. The preparation method according to claim 1, characterized in that: In step S2, the parameters of the drying process are as follows: temperature is 40° C., and time is 12 h.

10. The preparation method according to claim 1, characterized in that: In step S2, the parameters of the calcination treatment are as follows: temperature is 700° C., time is 2 h, and atmosphere is argon.

Citation Information

Patent Citations

  • Preparation method of carbon-coated photothermal conversion nano material

    CN103803632A

  • Hollow tubular nano material as well as preparation method and application thereof

    CN108975414A

  • Process for the sulfatization of non-ferrous metal sulfides

    US4541993A

  • Metal sulfide negative electrode material for sodium ion battery, and preparation method therefor

    WO2023071394A1

  • Carbon-coated nitrogen-doped cu 9s 5, and preparation method therefor and use thereof

    WO2023160102A1